Total replacement of the soybean meal with extruded semi-whole soybean in the piglets feeding during the nursery phase - Maria Eliza Brumatti Galiardi; Jansller Luiz Genova; Paulo Levi de Oliveira Carvalho; Isabela Ferreira Leal; Petrônio Pinheiro Porto; Liliana Bury de Azevedo dos Santos; Diovani Paiano; Marcos Augusto Alves da Silva (Semina: Ciências Agrárias, 2019)
The objective of this study was to evaluate the total replacement of soybean meal (SM) with extruded semi-whole soybean (ESWS) and its effects on feed digestibility, growth performance, plasma urea concentration (PUC) and economic feasibility. In Experiment I, a digestibility assay was undertaken using 12 crossbred pigs with an initial average body weight (IABW) of 18.85 ± 0.69 kg, distributed in a completely randomized design (CRD), with two treatments (reference diet and replacement of 30% of the reference diet by ESWS), six replicates and one pig per experimental unit. Experiment II involved 64 crossbred piglets, entire males, with an IABW of 7.46 ± 0.55 kg, distributed in a CRD, with two treatments (a control diet containing SM and another in which ESWS replaced SM), eight replicates and four animals per experimental unit. The digestible contents of dry matter, crude protein and gross energy of ESWS were 91.26%, 42.21% and 4,629 kcal kg -1, and the digestibility coefficients were 92.33%, 96.49% and 91.21%, respectively. Experiment II data indicated an effect on the feed conversion (FC) in the total period, in which pigs fed SM presented better FC. The diets affected the PUC in the pre-starter II phase and the total period, with pigs fed SM showing higher PUC. The cost of feed per kilogram of live weight gain increased in the starter phase. ESWS does not change the DWG and ADFI of piglets but worsens both the FC in the total period and economic results.